2001
DOI: 10.1002/dmrr.235
|View full text |Cite
|
Sign up to set email alerts
|

Lower incidence of severe hypoglycaemia in patients with type 2 diabetes treated with glimepiride versus glibenclamide

Abstract: In people with type 2 diabetes, glimepiride was associated with fewer episodes of severe hypoglycaemia than glibenclamide in routine clinical use. However, severe hypoglycaemia did occur with glimepiride and may be minimised if treatment targets are determined on an individual basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
0
23

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(130 citation statements)
references
References 24 publications
5
102
0
23
Order By: Relevance
“…Episodes can be both prolonged and life threatening, although these are very rare. Several of the newer sulfonylureas have a relatively lower risk for hypoglycaemia (Table 1) [45,46]. In [47].…”
Section: Principles In Selecting Antihyperglycaemic Interventionsmentioning
confidence: 99%
“…Episodes can be both prolonged and life threatening, although these are very rare. Several of the newer sulfonylureas have a relatively lower risk for hypoglycaemia (Table 1) [45,46]. In [47].…”
Section: Principles In Selecting Antihyperglycaemic Interventionsmentioning
confidence: 99%
“…19,25 Glimepiride on the other hand has favourable pleiotropic cardiovascular effects, low incidence of hypoglycaemia and is the preferred sulfonylurea in obese patients. [26][27][28] Analysing FPG and HbA1C values, pre-treatment and 1 year post treatment of 5 commonly prescribed treatment groups showed that all treatment regimens showed significant reduction in FPG except metformin monotherapy. Fasting plasma glucose is a highly unreliable value for assessing glycemic control since it is dependent on previous day's diet, medication and exercise.…”
Section: Discussionmentioning
confidence: 99%
“…However, severe episodes are relatively more frequent in the elderly. Chlorpropamide and glibenclamide (known as glyburide in the USA and Canada), are associated with a substantially greater risk of hypoglycaemia than other second-generation sulfonylureas (gliclazide, glimepiride, glipizide, and their extended formulations), which are preferable (Table 1) [53,54]. In addition, weight gain of~2 kg is common following the initiation of sulfonylurea therapy.…”
Section: Medicationsmentioning
confidence: 99%